2012
DOI: 10.1007/s10841-012-9492-1
|View full text |Cite
|
Sign up to set email alerts
|

All natural habitat edges matter equally for endangered Maculinea butterflies

Abstract: An obvious consequence of habitat fragmentation is an increasing role of habitat edges for species survival. Recently it has been suggested that the endangered butterfly Maculinea nausithous prefers forested edges of its meadow habitats. However, the prevalence of forests in the study area used for this analysis makes it impossible to distinguish whether the effect detected is a genuine preference for forest edges or a preference for any natural patch edges as opposed to patch interiors. We investigated habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The proximate mechanism behind the reduced emigration is probably butterfly tendency to avoid crossing habitat patch edges bordered by forest. Although Maculinea butterflies do not refrain from the edges of their habitat patches, and may even prefer to use the edges (Batáry et al 2009;K} orösi et al 2012;Nowicki et al 2013), they have been found to avoid crossing the edges, especially high contrast ones. Among various types of patch edges examined by Skórka et al (2013), forest ones were crossed the least frequently by M. teleius.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximate mechanism behind the reduced emigration is probably butterfly tendency to avoid crossing habitat patch edges bordered by forest. Although Maculinea butterflies do not refrain from the edges of their habitat patches, and may even prefer to use the edges (Batáry et al 2009;K} orösi et al 2012;Nowicki et al 2013), they have been found to avoid crossing the edges, especially high contrast ones. Among various types of patch edges examined by Skórka et al (2013), forest ones were crossed the least frequently by M. teleius.…”
Section: Discussionmentioning
confidence: 99%
“…Although mark-recapture studies were also carried out in the investigated metapopulations in other years, they were not comprehensive enough for dispersal analysis, because they were limited to too few local populations (cf. Stettmer et al 2001;Nowicki et al 2013). A clear exception in this respect was the metapopulation near the Czech town of Přelouč, which was intensively surveyed for seven consecutive years (Nowicki and Vrabec 2011).…”
Section: Study Species and Their Field Surveysmentioning
confidence: 99%
“…dimension 90 m) were located close to each other and were surrounded mostly by meadows without S. officinalis and high reeds. A more detailed description of the study sites can be found elsewhere [20,21]. Patch K9 was investigated only in 2003.…”
Section: Field Samplingmentioning
confidence: 99%
“…Although quarry operations represent a dramatic land degradation; shortly after their abandonment spontaneous succession turns them into diverse habitat mosaics supporting a rich butterfly fauna (Novák and Konvička 2006;Tropek et al 2010Tropek et al , Č ermáková et al 2010. A similar situation can be observed in other artificial environments especially those created by infrastructure development, such as road margins, railway embankments, gravel pits, or ruderal habitats in suburbia (Van Geert et al 2010;Lenda et al 2012;Moron et al 2014;Nowicki et al 2013). Nevertheless, it must be underlined that such man-made environments offer favourable conditions only in their early successional stages, hence only in the short-term, and later on they require management just like natural habitats in order to prevent overgrowing.…”
Section: Discussionmentioning
confidence: 66%